Associations of parental factors with screen time among preschool-age children: a cross-sectional survey - Chunmei HU; Xiao LÜ; Lingling HE (Editorial Office of Chinese Journal of Public Health, 2023)
Objective To investigate the relationship between screen time and parental factors among preschool-age children, and to provide a reference for reducing screen time and improving screen time compliance rate in the children. MethodsA self-administered questionnaire survey was conducted among the parents of 1 300 preschool-age children recruited with convenience sampling from 4 kindergartens in 2 districts of Chongqing municipality during May - June 2021. The screen time of a child was assessed based on separate report of father and mother and the cumulative time of ≤ 1 hour per day was considered as an appropriate screen duration for a child, which was recommended in the Physical Exercise Guideline for 3 - 6 Year Children established by domestic researches. The Internet Addiction Scale and the Parental Indulgence Questionnaire were also used. Logistic regression model was adopted to analyze the relationship between parental factors and screen time of preschool-age children. Results Valid responses were collected from the parents of 1 180 (90.77%) of the children selected. Of the children with valid information, 62.3% were reported having the cumulative screen time of ≤ 1 hour per day; the proportion differed significantly by residential region and parental education (both P < 0.01), with the higher proportion of urban children than that of rural children (68.2% vs. 57.1%) and higher proportions of the children with paternal/maternal education of college and above compared to the children with the paternal/maternal education of senior high school and below (68.9% vs. 56.2%/66.2% vs. 58.9%), respectively. The results of multivariate logistic regression analysis showed that the children with following parental characteristics were more likely to have an inappropriate screen time: with the paternal education of senior high school and below (odds ratio [OR] = 1.744, 95% confidence interval [95%CI]: 1.278 - 2.463), with a longer paternal screen time (OR = 1.229, 95%CI: 1.126 - 1.340), and with a longer maternal screen time (OR = 1.104, 95%CI: 1.026 - 1.187). ConclusionParental factors are of significant influence on screen time of preschool-age children. Comprehensive interventions should be promoted to control preschool-age children's screen time.